Misfit Layer Compounds: A Platform for Heavily Doped 2D Transition Metal Dichalcogenides. (6th November 2020) - Leriche, Raphaël T.; Palacio‐Morales, Alexandra; Campetella, Marco; Tresca, Cesare; Sasaki, Shunsuke; Brun, Christophe; Debontridder, François; David, Pascal; Arfaoui, Imad; Šofranko, Ondrej; Samuely, Tomas; Kremer, Geoffroy; et al.
Abstract: Transition metal dichalcogenides (TMDs) display a rich variety of instabilities such as spin and charge orders, Ising superconductivity, and topological properties. Their physical properties can be controlled by doping in electric double‐layer field‐effect transistors (FET). However, for the case of single layer NbSe2, FET doping is limited to ≈ 1 × 10 14 cm −2, while a somewhat larger charge injection can be obtained via deposition of K atoms. Here, by performing angle‐resolved photoemission spectroscopy, scanning tunneling microscopy, quasiparticle interference measurements, and first‐principles calculations it is shown that a misfit compound formed by sandwiching NbSe2 and LaSe layers behaves as a NbSe2 single layer with a rigid doping of 0.55–0.6 electrons per Nb atom or ≈ 6 × 10 14 cm −2 . Due to this huge doping, the 3 × 3 charge density wave is replaced by a 2 × 2 order with very short coherence length. As a tremendous number of different misfit compounds can be obtained by sandwiching TMDs layers with rock salt or other layers, this work paves the way to the exploration of heavily doped 2D TMDs over an unprecedented wide range of doping. Abstract : A misfit compound formed by sandwiching NbSe2 and LaSe layers is studied via STM and ARPES measurements combined with first‐principles calculations. The misfit material behaves as a NbSe single layer with a rigid doping 0.6 electrons per Nb atom or 10 14 cm −2 . This huge doping is way beyond what can be achieved by conventional doping.